Proceedings of the 10th International Conference on Human Computer Interaction With Mobile Devices and Services 2008
DOI: 10.1145/1409240.1409338
|View full text |Cite
|
Sign up to set email alerts
|

United-pulse

Abstract: This paper introduces a device that creates remote intimacy by the use of two rings named "united-pulse". Each ring can measure the wearer's heartbeat and send it to the partner's ring. Hereby, artificial corporeality is created between the couple. By means of a working prototype, united-pulse has been successfully tested. Among the 28 participants the prototype has attracted large interest. Through the heartbeat -the essential vital sign -a feeling of being very close to the partner is provided. Touching the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Research has also shown that expressive biosignals can affect closeness with others. For instance, systems such as rings or smartwatches where you can feel or see a partner's heart rate can improve feelings of being connected with remote friends and family [49,51,56,63,69]. Janssen and colleagues demonstrate that biosignals can also increase feelings of closeness with strangers.…”
Section: Expressive Biosignals and Interpersonal Closenessmentioning
confidence: 99%
“…Research has also shown that expressive biosignals can affect closeness with others. For instance, systems such as rings or smartwatches where you can feel or see a partner's heart rate can improve feelings of being connected with remote friends and family [49,51,56,63,69]. Janssen and colleagues demonstrate that biosignals can also increase feelings of closeness with strangers.…”
Section: Expressive Biosignals and Interpersonal Closenessmentioning
confidence: 99%
“…They found through the study that participants used the shared heart rates to communicate with others and they then felt strong connectedness to others by understanding their condition through the heart rates. Werner proposed a United-pulse (Werner et al, 2008), which is a ring type device that could measure pulse waves and vibrate, to share heartbeats. Lotan developed an Impulse system (Lotan et al, 2007) that measured pulse waves and vibrated, and allowed users to wirelessly transmit their heartbeat rhythms to an audio speaker and a lamp.…”
Section: Sharing Physiological Signalsmentioning
confidence: 99%
“…Similarly to the Whisper Pillow, many concepts aim at supporting emotional expression through "tangibility". Examples are vests (e.g., [20]), dolls or teddy bears (e.g., [29]), belts (e.g., [8]), finger rings (e.g., [31], or wrist bands (e.g., [22]) to transfer the partner's pulse [31], gestures, such as a hug (e.g., [13,19,29]). Hugvie, for example, is a human shaped pillow, to be hugged while talking to the partner via cell phone (the cell phone is embedded in Hugvie's head).…”
Section: Figure 1: Whisper Pillowmentioning
confidence: 99%